106 Stentolith As an Uncommon Complication of Loss to Follow Up After Endoscopic Biliary Stenting. (12th October 2021) - Ng, S; Lam, M; Gil, N; Shamali, A
Abstract: Introduction: Endoscopic biliary stenting is a common procedure, with indications from malignant obstruction to benign stone disease. We discuss a patient who re-presented after endoscopic stenting having been lost to follow up, with a large 'stentolith' requiring open CBD exploration. Case Presentation: A 56-year-old female presented in 2013 with obstructive jaundice and a 2-week history of abdominal pain. She was a smoker, but otherwise had no past medical, surgical, or relevant family history. After initial workup, ERCP with sphincterotomy and pigtail stent placement was performed with interval laparoscopic cholecystectomy in 2014. Post-operative follow up was not arranged, and the patient subsequently re-presented in 2020 with fatigue. MRCP confirmed a proximal CBD stone and linear artefact. Open exploration facilitated removal of the stone-stent complex. Discussion: Complications of stenting include cholangitis, stent occlusion and migration [2]. Stenting for failed biliary stone extraction is considered a temporary measure, with removal or exchange at three months (1). However, patients may be lost to follow up and return with non-specific symptoms. A rare cause is de novo formation of a gallstone calculus encasing the stent, a phenomenon termed "stentolith" [4]. Proposed pathophysiology is through promotion of bacterial proliferation by the stent, with biofilm formation and calcium bilirubinate precipitation [6]. Variation in formation has been described, with plastic stents developing circumferential stones [12-25], due to potential space between the wall and stent. Conclusions: This highlights the importance of robust inter-disciplinary working; careful patient follows up and implementation of a mandatory registry at all hospitals for stented patients.